The Influence of Discipline on Lecturers’ Motivation and Performance in Indragiri College of Economics (STIE) Rengat - Ivalaina Astarina; Hapsila, Angga; Fitrio, Tomy (International Journal of Scientific Research and Management (IJSRM), 2019)
This research aimed to determine the influence of discipline on motivation, as well on lecturers’ performance, and to discover the influence of motivation on the lecturers’ performance in Indragiri College of Economics (STIE) Rengat. The researchers took the population of the lecturers in Indragiri College of Economic (STIE-I) Rengat. The numbers of the lecturers in Indragiri College of Economics (STIE) Rengat were 34 people. The sampling method of this research was using a saturated sampling technique (census). The data of this research were analyzed by using quantitative method and all obtained data were processed by PLS. The results of this research showed that discipline had significant influence on motivation, as well on the lecturers’ performance; subsequently the motivation had influence on the lecturers’ performance and discipline had influence on the lecturers’performance which was mediated by motivation.